Horse Preferences for Insolation, Shade or Mist Curtain in the Paddock under Heat Conditions: Cardiac and Behavioural Response Analysis - Iwona Janczarek; Anna Stachurska; Izabela Wilk; Anna Wiśniewska; Monika Różańska-Boczula; Beata Kaczmarek; Jarosław Łuszczyński; Witold Kędzierski (Animals, 2021)
The horse’s welfare and, consequently, the emotional arousal may be connected with stressful environmental conditions. This study aimed to determine whether horses show behavioural or physiological symptoms of thermal discomfort and if their behaviour and cardiac parameters are related to freely chosen insolated (IS), shaded (SH), or water sprayed (with a mist curtain (MC)) areas in a paddock under heat conditions (29–32 °C, 42.0 ± 1.5% humidity). Twelve adult horses freely moving in the paddock were studied during a 45 min solitary turnout. Six cardiac variables, locomotor, and non-locomotor activities as well as rectal temperature before and after the test were monitored with regard to the area of staying. Horses did not show clear preferences regarding the time spent in IS, SH, and MC, although preferences of particular horses differed considerably. When staying under IS and MC conditions, the horses showed a higher level of relaxation compared to SH. Horses did not exhibit symptoms of thermal discomfort while staying in the sun. Free choice between the three areas differing in environmental conditions could be a crucial factor in maintaining body temperature as well as emotional arousal at similar levels. Thus, the provision of a shade and mist curtain in paddocks seems to be reasonable.